The impact of cadmium and mercury contamination on reproduction and body mass of earthworms - S. Lapinski; M. Rosciszewska (Plant, Soil and Environment, 2008)
The accumulation of heavy metals in the tissues of earthworms is a helpful indicator of environmental contamination. The degree of substrate contamination can be additionally evaluated on the basis of survivability, reproduction and body mass of earthworms. In this study Eisenia fetida Sav. earthworms were exposed to a series of increasing concentrations of cadmium and mercury. The numbers of animals and their body mass were checked after 4 and 8 months. The strongest impact of substrate contamination was exerted upon the number of young individuals and cocoons. The cadmium contamination did not affect adversely the mass of earthworms, whereas in the mercurycontaminated group the decline in body mass was evident. After 8 months of experiments, the content of heavy metal in the bodies of earthworms was determined. An evident relationship between the cadmium and mercury contents in the substrate and their accumulation in earthworms' tissues was found. The concentration in the bodies exceeded the level in the substrate.